The performance of Acacia xanthophloea, Schinus molle, Casuarina equisetifolia and Grevillea robusta in the rehabilitation of a limestone quarry at East African Portland Cement Factory, Athi River, Kenya (Geo-Eco-Marina, 2017)
Limestone remains the most exploited and crucial industrial mineral worldwide, hence mining activities within limestone quarries will imminently prevail. Quarrying for limestone is an economic necessity that is not only hazardous to humans but also one that invariably has deleterious effect on the environment. Information on the performance of tree species is important as plants are key in the revegetation of exhausted quarries. A comparison of field performance of Acacia xanthophloea, Schinus molle, Casuarina equisetifolia and Grevillea robusta was made in an exhausted limestone quarry in a semi-arid area, in Athi River, Kenya. The exhausted quarry was backfilled with the mine waste material and then leveled. Four blocks, each 25 m x 25 m, were established at the quarry site for tree planting and control, using the Randomized Complete Block Design (RCBD). Six months old seedlings of each species produced in a nursery were transplanted in the plots. The sequence of planting the four species was varied from block to block. One block was left unplanted for control. Growth performances were estimated by measuring tree height, diameter at the stem base (BD), and diameter at breast height (DBH). Seedling height (cm) and stem diameter (cm) were measured immediately after planting, and thereafter measurements were recorded every two weeks for a period of two years. To avoid border effect, the height and diameter of the middle 10 trees of each species in each block were measured, as these were less susceptible to external influence. The tree height from ground level to tip of the youngest leaf was determined using a tape measure. A Vernier caliper was used to measure basal stem diameter 1 cm above the soil surface. A line was painted on the trunk, to ensure repeat measurements are made at the same point for the diameter. To maintain consistency during data collection, a similar method was used for measurements of diameter at breast height (1m above soil). This commenced at the beginning of year II of planting when most trees had attained a height of at least 1.3 m. Diameter at breast height was measured immediately below a branch if this occurred at a height of 1 m. The study revealed that the time-species interaction was significant (p
Keywords: Mining; Rehabilitation; Tree Species; limestone quarry